“El encebollado de la Otto” en la ciudad de Babahoyo con servicio a domicilio - Ochoa Carranza, Karen Denis (2020)
The present qualification work is to publicize the implementation of a service which will feasibly and profitably favor the seafood restaurant "EL ENCEBOLLADO DE LA OTTO" in the city of Babahoyo. This business is dedicated to the preparation and sale of onion dishes, among these are the simple albacore onion, mixed onion, which is made up of different seafood such as shrimp, mussels, squid, octopus, crab pulp and especially the albacore, and the shrimp onion. It should be noted that the client can order his onion as he prefers, one of the purposes of the seafood restaurant is to please him. Additional products are also offered to accompany the product, such as muffins, bread, avocado and soft drinks. The action plan that will be carried out for the development of this business idea is based on each chapter. Chapter I will introduce the business idea to be implemented, theoretically supporting each of the concepts. On the other hand, the market study will be carried out, diagnosing the target audience to be satisfied. In Chapter II you will find the organizational design of the enterprise, description, managerial foundation and functional and organizational structure. In Chapter III, the business model is validated using the CANVAS methodology, describing and analyzing each point to determine the degree of feasibility of the venture. In chapter IV the feasibility studies of the undertaking are developed. As number one is technical feasibility, in which the resources and elements that will intervene in the business will be established. Then there is the financial feasibility, here the working capital, investment budget, amortizations, remunerations, cash flow, internal rate of return, and the net present value will be disclosed. The strategic processes and procedures that will be used to provide product service will also be established through the operational feasibility study. And as every new business or venture in the market wants to know how it will influence the environmental and social aspect, you will find in this chapter, the feasibility studies of these. As a last point will be the recommendations of the case that will be given after the study carried out and, therefore, where it is concluded